Mineralogy of scapolite from Skallen in the Lutzow-Holm Bay region, East Antarctica - Kusachi, Isao; Osanai, Yasuhito; Toyoshima, Tsuyoshi; Owada, Masaaki; Tsunogae, Toshiaki; Hokada, Tomokazu; Crowe, Warwick A. (National Institute of Polar Research, 1999)
P(論文) Two types of zoned scapolite in calc-silicate gneisses from Skallen, East Antarctica, were found. One type varies from Me_<79> in the core to Me_<35> at the rim. Associated minerals are mainly diopside, pargasite and spinel. The other varies from Me_<33> in the core to Me_<57> at the rim. Associated minerals are mainly diopside, phlogopite and K-feldspar (Or_<95-99>). Scapolite in this specimen contains characteristically K, and the substitution of K in the M site is 8-12%. The unit cell dimensions of scapolite (Me_<42-45>) from Skallen are a=12.121 (1), c=7.585 (2) A, and those (Me_<77-83>) from Sri Lanka are a=12.164 (1), c=7.568 (1) A. These scapolites belong to different isomorphous series. It is likely that the zonation and K-substitution of scapolites from Skallen appear to be formed by a reaction with minerals in direct contact and/or fluids in later stage alteration. departmental bulletin paper